2021
DOI: 10.1097/md.0000000000024034
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis of fetal congenital mesoblastic nephroma by ultrasonography combined with MR imaging

Abstract: Rationale: Fetal congenital mesoblastic nephroma (CMN) is a rare renal tumor, characterized by polyhydramnios, premature birth, and neonatal hypertension. In the prenatal stage, it is particularly difficult to diagnose CMN either by ultrasonography or magnetic resonance imaging (MRI). Thus, CMN is frequently detected in the third trimester in the clinical scenario. Patient concerns: A 29-year-old G2P0 pregnant woman took routine prenatal examinations in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Following abstract screening, 102 articles were determined to be outside the scope of the investigation and a further 14 full-text articles described cases of abdominal tumours without concomitant polyhydramnios. The remaining 27 publications describing 32 cases constituted the basis of this review ( Supplementary Table S1 ), [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Following abstract screening, 102 articles were determined to be outside the scope of the investigation and a further 14 full-text articles described cases of abdominal tumours without concomitant polyhydramnios. The remaining 27 publications describing 32 cases constituted the basis of this review ( Supplementary Table S1 ), [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, both the adrenal glands and contralateral kidney should be meticulously visualized. If highly suspected, MRI can be helpful to evaluate the origin and morphological characteristics of a fetal abdominal mass [ 8 , 10 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…CMN can be prenatally diagnosed by ultrasound and MRI. Several case/series reports of the prenatal diagnosis of CMN have been scatteringly published in the literature, and they are increasing in number [ 2 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. However, to the best of our knowledge, the prenatal features and outcomes of pregnancies with fetal CMN have never been systematically reviewed and analyzed, whereas neonatal and pediatric series have been published several times.…”
Section: Introductionmentioning
confidence: 99%
“…However, CMN is the most common benign tumour in the first six months of life ( 2 ). However, most studies on foetal CMN are case reports ( 9 – 12 ). Lin et al reported the first case of live birth diagnosed with foetal CMN in Taiwan.…”
Section: Discussionmentioning
confidence: 99%